A single intravenous reelin injection restores corticosterone-induced neurochemical and behavioral alterations in dams during the post-partum period - Sánchez-Lafuente, Carla L.; Johnston, Jenessa N.; Reive, Brady S.; Scheil, Kaylene K. A.; Halvorson, Ciara S.; Jimenez, Mariana; Colpitts, Darian; Kalynchuk, Lisa E.; Caruncho, Hector J. (Frontiers in Molecular Neuroscience, 2024)
IntroductionTreatment with the synaptic plasticity protein reelin has rapid antidepressant-like effects in adult corticosterone (CORT)-induced depressed rats, whether administered repeatedly or acutely. However, these effects remain unexplored in the context of post-partum depression (PPD).MethodsThis study investigated the antidepressant-like effect of a single injection of reelin in a CORT-induced model of PPD. Long-Evans female dams received either daily subcutaneous CORT (40 mg/kg) or saline injections (controls) from the post-partum day (PD) 2 to 22, and on PD22 were treated with a single intravenous reelin (3 μg) or vehicle injection.ResultsReelin treatment fully normalized to control levels the CORT-induced increase in Forced Swim Test (FST) immobility and the decrease in reelin-positive cells in the subgranular zone of the intermediate hippocampus. It also increased the number of oxytocin-positive cells in the paraventricular nucleus (PVN), the number of reelin-positive cells in the dorsal and ventral hippocampus, and the dendritic complexity of newborn neurons in the intermediate hippocampus, causing a partial recovery compared to controls. None of these changes were associated with fluctuations in estrogen levels measured peripherally.DiscussionThis study brings new insights into the putative antidepressant-like effect of peripherally administered reelin in an animal model of PPD. Future studies should be conducted to investigate these effects on a dose–response paradigm and to further elucidate the mechanisms underlying the antidepressant-like effects of reelin.